Chlorine is preferred over bisulfite for H2O2 quenching following UV-AOP drinking water treatment. (15th November 2019) - Wang, Chengjin; Hofmann, Michael; Safari, Armin; Viole, Isabelle; Andrews, Susan; Hofmann, Ron
Abstract: Drinking water treatment using UV/H2 O2 advanced oxidation typically results in residual H2 O2 that requires quenching to minimize its interference with downstream processes. Chemical quenching using chlorine or bisulfite are options, but there is some uncertainty in the literature about the kinetics of the bisulfite reaction, with some reports quoting the reaction as fast, and others as slow. Part of the contradictory information may be due to interference in H2 O2 analysis by bisulfite. An analytical method was developed to avoid this interference, in which monochloramine first selectively quenched bisulfite, and then H2 O2 was measured spectrometrically using titanium(IV) oxysulfate for color development. The confirmatory experiments suggested that the bisulfite reaction with H2 O2 is actually relatively slow, with a half-life in the order of hours to days depending on the pH and the reagent concentrations. As a result, within the typical pH range of drinking water treatment (e.g., 6–9), chlorine is preferred over bisulfite as the H2 O2 quenching agent on the basis of reaction kinetics. However, a decrease in pH will lead to an increase in the bisulfite-H2 O2 reaction rate along with a decrease in the Cl2 –H2 O2 reaction rate, such that at pH < 5.7 bisulfite is the faster reagent. Both bisulfite and chlorine were observed to react with H2 O2 following a stoichiometric ratio of 1:1 in the natural water matrix tested. Graphical abstract: Image 1 Highlights: Bisulfite quenches H2 O2 at too slow a rate to serve as a quenching agent. Cl2 quenches H2 O2 quickly at neutral and basic pH, but not instantaneously. A modified titanium(IV) method was developed to quantify H2 O2 .